Orchid florula of Parque Nacional Manuel Antonio, Quepos, Costa Rica - Pupulin, Franco (Universidad de Costa Rica, 1998)
An orchid florula of Parque Nacional Manuel Antonio, Costa Rica, is provided on the basis of collections made in 91 p1ots within the park and field observations carried out in the neighbouring areas; 39 species belonging to 25 genera are recorded. Orchid species are described and a key to the species for field identification, based on vegetative features, is provided. Analytica1 drawings are provided for 35 of the taxa considered. Ecological notes and estímate of frequency for each species within the Park are given. A new orchid species, Lockhartia pandurata, is described and illustrated.